The Web-Based Usability Heuristic Survey Supports User Satisfaction - Wijayanto, Emanuel; da Costa Tavares, Ofelia Cizela; dos Santos, Apolinario (Indonesian Journal of Information Systems, 2020)
Competition between companies is now getting stronger strongly related to the company's mechanism in providing the services provided. Companies can build ways that can maintain customer loyalty. The approach can be done with web-based Usability Testing adopting an application user acceptance model, a usability aspect analysis that acts as a customer who enjoys a company's products and services. At present, there are already many theories of user acceptance models for an application. One of them is the user satisfaction model (User Satisfaction). This review specifically also identifies that content content has a significant positive effect on website visitor satisfaction.